Evaluation of combined hepatocellular-cholangiocarcinoma using CEUS LI-RADS: correlation with pathological characteristics. - Bao, Jingwen; Nie, Zehua; Wang, Quanwen; Chen, Yanling; Wang, Kun; Liu, Xinjiang (Abdominal Radiology, 2025)
Objective: To explore the factors that influence the contrast-enhanced ultrasound (CEUS) Liver Imaging Reporting and Data System (LI-RADS) classification of combined hepatocellular-cholangiocarcinoma (cHCC-ICC). Methods: Between September 2014 to July 2020, the CEUS features of 58 patients with pathologically confirmed cHCC-ICC were retrospectively evaluated and assigned according to the CEUS LI-RADS (version 2017). The pathological characteristics of nodules categorizing as different CEUS LI-RADS categories were compared. Multivariate logistic regression analysis was conducted to explore potential factors that may influence the CEUS LI-RADS classification of cHCC-ICC. Results: According to CEUS LI-RADS, 32.8% (19/58), 63.8% (37/58), and 3.4% (2/58) were categorized as LR-5, LR-M, and LR-TIV, respectively. There was significant difference between the LR-M and LR-5 groups with regard to the pathological grade, nodule size, and HCC/ICC-component ratio of cHCC-ICC. Multivariate logistic regression analysis identified tumor size and the relative proportions of hepatocellular carcinomas (HCC) and intrahepatic cholangiocarcinomas (ICC) components as the independent influencing factors. Conclusion: Tumor size and the relative proportion of HCC and ICC components within the nodule had a significant impact on the CEUS LI-RADS classification of cHCC-ICC. Key points: Tumor size and the relative proportions of HCC and ICC components were the independent influencing factors for the CEUS LI-RADS classification of cHCC-ICC. The HCC/ICC-component ratio acted on the CEUS LI-RADS classification mainly through influencing the enhanced pattern of nodules. Tumor size mainly had an impact on the enhanced pattern and washout features of cHCC-ICCs, thus leading to different CEUS LI-RADS classification.